Keteraturan Kunjungan Antenatal Care Dengan Pendekatan Kohort Study Di Puskesmas Banjar I - Ni Nengah Yunariasih; putu dian prima kusuma dewi; Indrie Lutfiana (2022)
High-risk pregnancy is one of the conditions that can indirectly or directly harm the condition of the mother and baby, which can be prevented if the risk in pregnancy is detected early. In reality, pregnant women who are at high risk or low risk rarely make regular antenatal care visits, so the information they have about risky pregnancies and the importance of antenatal visits is still lacking. The schedule of visit examinations for high-risk pregnant women is carried out more regularly and regularly in accordance with the nature of the risk factors that exist in pregnant women and supporting examinations that need to be carried out. This study aims to look at gestational and clinical characteristics in pregnant women at risk. Research is a descriptive quantitative research with a cohort study and a retrospective approach. This descriptive research was used to examine the incidence of pregnancy at risk at the Banjar I Health Center by utilizing the maternal cohort register in the last 1 (one) year. The results showed that the low-risk pregnancy category was 80.7% (343/425) while the high-risk category was 19.29% (82/425). Gestational characteristics in pregnant women with low risk, healthy reproductive age of 88.34% (303), distance less than 2 years 55.10% (189) with an average age of 38.9 weeks while the high risk group with unhealthy reproductive age of 68.29% (56), distance of more than 2 years 80.49% (66) with an average gestational age of 39.02 weeks. ANC visits in the irregular category with criteria of more than 30 days i.e. on visits 1 to 2 (293: 68.94%), Visits 2 to 3 (294: 69.18%), visits 3 to 4 (287: 67.53%), visits 4 to 5 (253: 59.53%). The results of this study can be used as input for midwives in order to provide the right IEC and carry out early detection in every pregnancy.